PENGRUH LATIHAN NUMBER DRILL TERHADAP KELINCAHAN PADA SISWA KELAS VIII EKSTRAKURIKULER SMP NEGERI 25 PEKANBARU - Muhammad Hadi Putra Hadi Putra; Slamet '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: The problem in this study, that agility In Eighth Grade Students Extracurricular SMP 25 Pekanbaru less than the maximum. This is presumably due to the lack of rapid motion also fast enough to make a change in body position to do other  different movements. The purpose of this study is to look at the effects of exercise on agility Number Drill In Eighth Grade Students Extracurricular SMP 25 Pekanbaru. This research is a quasi experiment to see the effects of this form of exercise. The population in this study are all Grade VIII, totaled 15 people. The sampling technique is by sampling saturated, meaning that in which the entire population sampled is the sample in this study amounted to 15 people. Instrument in this study using the Illinois Agility Test to see agility. Analyses were performed using t-test. The research concludes that the influences of exercise Number Drill for Students of Class VIII agility Extracurricular SMP 25 Pekanbaru with to ttest 9.60 > ttable 1.761 at α = 0.05. Keywords: Number Drills and Agility